Fasting glucose concentrations and associations with reproductive history over 40 years of follow-up. (3rd August 2018) - Wallace, Maeve E.; Bazzano, Lydia; Zhang, Cuilin; Harville, Emily
Abstract: Gestational diabetes mellitus (GDM) is the onset or first recognition of diabetes that occurs during pregnancy. We aimed to assess for trends in fasting blood glucose levels across the life-course among a cohort of women by reproductive history: nulligravid women, gravid women with and without a history of GDM. Women who had participated in the Bogalusa Heart Study as children were interviewed about their reproductive history, including GDM ( n = 358). We compared fasting blood glucose (mg/dL) measured after last pregnancy (or after age 40 among nulligravid women) across reproductive history groups in linear models adjusted for prepregnancy fasting blood glucose, body mass index, race, parity, and age at outcome measure. We fit a log-Poisson model to estimate the associations with prediabetes risk after age 40. After adjustments, mean fasting glucose after age 40 was not different between gravid women without GDM history and nulligravid women. However, women with a history of GDM had mean fasting glucose 27 mg/dL greater than nulligravid women (95% CI = 12.35, 41.64). Heterogeneity by race indicated Black women with a history of GDM had disproportionately elevated mean fasting glucose after age 40. Fasting blood glucose trends over the life-course differ among women by reproductive history and race.